2017
DOI: 10.18311/jsst/2017/16264
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Properties of Cu-based Alloy Manufactured by Self-Propagating High-Temperature Synthesis Method

Abstract: <p>Microstructure and properties of Cu<sub>1-x</sub>Zn<sub>1-y</sub>Al<sub>1-z</sub> ranging through (0.29 &lt;X&lt; 0.30; 0.74 &lt;Y&lt; 0.75; and 0.83 &lt;Z&lt; 0.96) alloys obtained by the Self- propagating High-temperature Synthesis (SHS) were examined. The microstructural and mechanical properties were examined, respectively by X-ray diffraction, tensile tests and Brinell hardness. The obtained results showed that the modification of compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rani et al prepared thin films of CdSe:Zn using Electron Beam (EB) evaporation technique [4]. Amiour et al investigated the microstructure and the shape memory related properties of Cu-Zn-Al alloys [5]. Their results revealed that any modification in the composition of the alloy led to the generation of new phases.…”
Section: Editor's Notementioning
confidence: 99%
“…Rani et al prepared thin films of CdSe:Zn using Electron Beam (EB) evaporation technique [4]. Amiour et al investigated the microstructure and the shape memory related properties of Cu-Zn-Al alloys [5]. Their results revealed that any modification in the composition of the alloy led to the generation of new phases.…”
Section: Editor's Notementioning
confidence: 99%